Early Postoperative Gait Analysis in Elderly Patients Following Hip Fracture Surgery - Gereon Anton Hecht; Rachel Senden; Rik Marcellis; Matthias Mertes; Paul Willems; Kenneth Meijer; Martijn Poeze; Taco J. Blokhuis (Sensors)
Hip fractures in elderly patients significantly reduce independence and quality of life. Early postoperative gait performance remains poorly understood, particularly regarding differences between surgical treatments, such as proximal femur nailing and hemiarthroplasty. Identifying gait alterations early in rehabilitation could optimize clinical interventions. This prospective observational cohort study included 40 elderly patients hospitalized after acute hip fracture surgery. Relative peak force and step duration were assessed using the ambulant pressure biofeedback system during postoperative mobilization. Additionally, three-dimensional gait analysis evaluated spatiotemporal parameters and sagittal plane kinematics of the hip, knee, and ankle. Results demonstrated significant improvements in median peak force (45.32% to 70.00%, (p < 0.001)) and median step duration (2.96 s to 137 s, (p < 0.001)) at the end of the hospitalization period. No significant differences in step duration and peak force were observed between the different surgical procedures, proximal femur nail, and hemiarthroplasty. Three-dimensional gait analysis showed significantly reduced hip extension during terminal stance in the operated leg compared to the healthy leg. These findings highlight the utility of biofeedback systems for monitoring early rehabilitation progress and emphasize the importance of 3D gait analysis in identifying early postoperative gait deficits. Targeted interventions during hospitalization could enhance functional recovery and improve patient outcomes.